Economic evaluation of adoption of improved soybean production and utilization technologies in Kaduna and Kano States Nigeria: P.hD. thesis - Ojiako, I.A. (2006)
Low yield, persistent pod shattering and susceptibility 10 pests and diseases characterize the cultivation of traditional soybean varieties in Nigeria. Research has, however, developed new improved variety of soybeans, like TGx 1448-2E that is cultivated in Kaduna and Kano States. Local food items that incorporate soybeans are equally used to improve the nutritional value of foods. This study investigates the socio-economic lac tors that influence the adoption of improved soybean innovations, examines gender roles in its production and utilization, and evaluates the impact of adoption of soybean technologies on household welfare in the two states. A multi-stage probability sampling design was used to draw the respondents. First, two Local Government Areas (LGAs) were randomly selected from a list of 20soybean-growing LGAs obtained for each state from ADP records. Second, three villages from Kaduna and two from Kano were selected from the listed soybean growing villages in the selected LGAs. Third, 201 households from Kaduna and 106from Kano were selected from the list of households in the included villages. A structured questionnaire and selected participatory rural appraisal (PRA) tools were used to elicit information from the respondents. The instruments covered household characteristics, yield, income-expenditure and input-cost profiles, and livelihood issues. Data were analyzed using descriptive and inferential statistics and Iobit regression analysis. In the two states, PRA reveals that men perform soybean production tasks while women engage in processing. One hundred and sixty-six households (54.0%) prefer the improved to local seeds for their sizes, colour, superior yield, and resistance to shattering, pests and diseases. Also, 60.9% adopted the improved technologies with more adopters from Kaduna than from Kano State. Yield, expenditure on labour, distance 10 market, association membership, and exposure to extension services significantly (P<0.01) influenced household decisions on adoption and use. One percent increase in yield and labour cost respectively result in 0.5% and 0.4%increases in probability of adoption and 0.6% and 0.5% in use intensity. Improved technologies resulted in significantly (P<0.05) higher average yield for adopters with an outcome of 1.2 tonnes per hectare as against 1.1 tonnes per hectare for non-adopters. Similarly, significant differences (P<O.GI) exist between the varieties in average farm gate price, output, and volume of sales. Inclusion of soybean in crop rotation enhances soil fertility, and soybean fanners' marginal yield of maize planted after soybean is 55.9 kg per hectare in favour of adopters. Financially, significant differences (P<O.05) in average income are obtained for acopters with an income of W7768.49 per year as against W6834.43 per year for non-adopters. On human capital, 49.2% adopters invest in children's education compared to 27.5% non-adopters due to higher income. Also, 61.5% adopters fall into the rich or middle class as against 54.2% for non-adopters. Eighty-five percent of women process at least one soybean incorporated food weekly for home use and earn between N2500.00 and N3500.00per week as profit. The adoption of soybean production and utilization technologies positively impacts on output and incomes of producers, female processors and, by extension, on promotion of household welfare. Therefore, soybean cultivation and use should be promoted as a policy option in Nigeria.